2012
DOI: 10.1105/tpc.112.101360
|View full text |Cite
|
Sign up to set email alerts
|

Opaque1 Encodes a Myosin XI Motor Protein That Is Required for Endoplasmic Reticulum Motility and Protein Body Formation in Maize Endosperm

Abstract: Myosins are encoded by multigene families and are involved in many basic biological processes. However, their functions in plants remain poorly understood. Here, we report the functional characterization of maize (Zea mays) opaque1 (o1), which encodes a myosin XI protein. o1 is a classic maize seed mutant with an opaque endosperm phenotype but a normal zein protein content. Compared with the wild type, o1 endosperm cells display dilated endoplasmic reticulum (ER) structures and an increased number of smaller, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
101
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 68 publications
4
101
0
1
Order By: Relevance
“…Four genes corresponding to recessive mutants, opaque1 (o1), o2, o5, and o7, have been cloned (Schmidt et al, 1990;Miclaus et al, 2011;Myers et al, 2011;Wang et al, 2011Wang et al, , 2012, the majority of which result from defects in storage protein synthesis, which affects endosperm texture. For example, O2 encodes a transcriptional factor that positively regulates the expression level of 22-kD a-zeins (Damerval and Devienne, 1993).…”
mentioning
confidence: 99%
“…Four genes corresponding to recessive mutants, opaque1 (o1), o2, o5, and o7, have been cloned (Schmidt et al, 1990;Miclaus et al, 2011;Myers et al, 2011;Wang et al, 2011Wang et al, , 2012, the majority of which result from defects in storage protein synthesis, which affects endosperm texture. For example, O2 encodes a transcriptional factor that positively regulates the expression level of 22-kD a-zeins (Damerval and Devienne, 1993).…”
mentioning
confidence: 99%
“…QPM has low levels of a-zeins, like o2, but the 27-kD g-zein is increased 2-to 3-fold (Wallace et al, 1990;Geetha et al, 1991;Lopes and Larkins, 1991;Holding et al, 2011); the degree of endosperm vitreousness closely correlates with the level of 27-kD g-zein protein , and this increase causes the observed elevation in protein body number in QPM Moro et al, 1995) consistent with the proposed role of 27-kD g-zein in protein body initiation. Some other opaque mutants are the result of aberrations in processes unrelated to protein bodies, such as amino acid biosynthesis, plastid development, and cytoskeletal function Myers et al, 2011;Wang et al, 2012). This indicates that further work is needed to generate a more complete understanding of the factors that control endosperm maturation.…”
mentioning
confidence: 99%
“…Furthermore, the possible role of the 50-kD g-zein in modification has not been previously addressed. The molecular characterization of opaque mutants has shown that vitreous endosperm formation depends on more than just correct abundance and spatial organization of zein proteins (Holding and Larkins, 2006;Holding et al, 2007Holding et al, , 2010Myers et al, 2011;Wang et al, 2012). Furthermore, mapping studies indicate there are several QTLs for endosperm modification in QPM Holding et al, 2008Holding et al, , 2011.…”
mentioning
confidence: 99%